2008
DOI: 10.21704/rea.v7i1-2.362
|View full text |Cite
|
Sign up to set email alerts
|

CRECIMIENTO Y SUPERVIVENCIA DE JUVENILES DE Argopecten purpuratus EN SISTEMAS DE FONDO Y SUSPENDIDO EN LA ZONA DE CASMA, PERÚ

Abstract: ResumenEste estudio compara el crecimiento y supervivencia de juveniles de Argopecten purpuratus "concha de abanico" cultivados en sistema de fondo y suspendido en la zona de Casma, AncashPerú. Del 29 de Julio y 21 de Octubre del 2006 se instaló un experimento usando "pearl nets" y corrales con individuos de 10mm (0.067g de parte blanda) a densidades de 816, 2450 y 4080 individuos/m 2 . Cada 2 semanas se colectaron 20 individuos y se registro la altura (mm) y peso de partes blandas (gramos) y mensualmente el n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Nevertheless, the pCO2 level of the present study was representative of the natural conditions found in the Peruvian upwelling system (Friederich et al, 2008). Furthermore, the experimental conditions (pH, temperature, and food) established in this study allowed us to achieve a growth rate in the control (0.33 mm d -1 ) that was close to those found in natural conditions, ranging range from 0.20 to 0.39 mm d -1 for individuals with a height of 10 to 23 mm (Aguirre, 2011;Alcazar and Mendo, 2008;Cisneros et al, 2008). Similarly, in a study carried out with A. purpuratus in Chile, Lagos et al (2016) achieved similar growth rates between the control and the natural growth rates of 0.08 to 0.17 mm d -1 that are found naturally in Chilean bays (Avendaño and Cantillanez, 2008;Ramajo et al, 2020).…”
Section: Experimental Conditions: Ph Of Control and Food Conditionsmentioning
confidence: 52%
“…Nevertheless, the pCO2 level of the present study was representative of the natural conditions found in the Peruvian upwelling system (Friederich et al, 2008). Furthermore, the experimental conditions (pH, temperature, and food) established in this study allowed us to achieve a growth rate in the control (0.33 mm d -1 ) that was close to those found in natural conditions, ranging range from 0.20 to 0.39 mm d -1 for individuals with a height of 10 to 23 mm (Aguirre, 2011;Alcazar and Mendo, 2008;Cisneros et al, 2008). Similarly, in a study carried out with A. purpuratus in Chile, Lagos et al (2016) achieved similar growth rates between the control and the natural growth rates of 0.08 to 0.17 mm d -1 that are found naturally in Chilean bays (Avendaño and Cantillanez, 2008;Ramajo et al, 2020).…”
Section: Experimental Conditions: Ph Of Control and Food Conditionsmentioning
confidence: 52%